The telling pool - Clement-Davies, David, 1961- (New York : Harry N. Abrams, 2006)
Relying on true courage and true love, as well as some surprising connections to the Arthurian legends, a young Welsh teenager named Rhodri embarks on a quest to remove an ancient curse from Great Britain during the reign of Richard the Lionheart.
Keywords: Coming of age -- Fiction; Arthur, -- King -- Fiction; Magic -- Fiction; Adventure and adventurers -- Fiction; Great Britain -- History -- Richard I, 1189-1199 -- Fiction